Impact of antipsychotic medication on IL‐6/STAT3 signaling axis in peripheral blood mononuclear cells of drug‐naive schizophrenia patients. Issue 1 (2nd November 2019) - Subbanna, Manjula; Shivakumar, Venkataram; Venugopal, Deepthi; Narayanaswamy, Janardhanan C.; Berk, Michael; Varambally, Shivarama; Venkatasubramanian, Ganesan; Debnath, Monojit
Abstract : Aim: Immunopathogenesis remains a widely appreciated etiopathological model of schizophrenia. Persistent efforts have aimed to identify schizophrenia biomarkers indexing immune system abnormalities and also immuno‐dampening effects of antipsychotic medications. Although data arising from published reports are encouraging, such studies are limited to a few immune parameters and not focused on a specific pathway. Th17 cells‐mediated immuno‐inflammatory responses have emerged as a potential mechanism in various neuropsychiatric conditions, including schizophrenia. The Th17 pathway is distinctly regulated through a coordinated action of multiple cytokines and transcription factors. In this study, we explored whether antipsychotic medication has any effect on the cytokines and transcription factors of the Th17 pathway. Methods: A total of 27 drug‐naive schizophrenia patients were recruited and followed up for 3 months after initiation of antipsychotic medication. Lymphocyte gene expression levels of two transcription factors ( STAT3 and RORC ) and one of their upstream regulators, IL6, were quantified before and after treatment. Plasma levels of cytokines, such as interleukin (IL)‐1β, IL‐6, IL‐17A, IL‐23, and IL‐33, were also analyzed before and after treatment. Results: Treatment with antipsychotic medication for 3 months resulted in significant downregulation of STAT3 gene expression as well as reduction in plasma levels of IL‐1β, IL‐6, and IL‐17A. Significant reduction in total scores for the Scale for Assessment of Positive Symptoms and the Scale for Assessment of Negative Symptoms was also observed in schizophrenia patients after 3 months of antipsychotic treatment. Conclusion: Our findings suggest possible immuno‐modulatory effects of antipsychotic medication on the critical regulators, such as IL‐6 and STAT3, of the Th17 pathway in schizophrenia patients. The IL‐6/STAT3 signaling axis involved in the transcriptional regulation of Th17 cells might appear as an important target of antipsychotic treatment in schizophrenia patients. Alternatively, irrespective of the effect of antipsychotic drugs, the IL‐6/STAT3 signaling axis might be crucially involved in ameliorating psychotic symptoms.